Consumer Behavior in Marketing Patterns, Types, Segmentation - Arshi Naim (European Science Publishing, 2023)
There are several decisions that consumers have to take throughout the day. These decisions many be insignificant but these decisions can make marketers to be awaken whole night to work on because decoding the processes behind customers’ decisions means that we can use that info to boost revenue. This study explains the importance of Consumer Behavior in marketing, the patterns, types and segmentation of consumers to plan the marketing strategies. This research studies CB for different products and services and how they decide on their purchase behavior. In this study, different aspects and facets of consumer behavior will be discussed and explains the most effective types of customer segmentation.
Keywords: Consumer Behavior, Consumer Segmentation, Marketing Strategies, Consumers Decisions